(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
It is emphasized that the education system is the initiator of changes to introduce gender equality in society. This, in turn, requires the development of a theoretical and methodological basis for the implementation and management of a gender approach to the education system. Therefore, this article, from a scientific point of view, examines the features of the implementation of a gender approach in higher education, the creation of equal rights and opportunities for women and men in higher education. One of the effective mechanisms for ensuring gender equality is the work of the Advisory Council on Equal Rights and Opportunities for Women and Men, created under the Ministry of Higher and Secondary Specialized Education. Analyzed the results of a survey on the provision of guarantees of equal rights and opportunities for women and men in the field of higher education. Dior guidelines have also been developed for integrating a gender perspective into the education system.